Cuban Education System and Teacher Education in Cuba - Betül Baldan (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
Cuba, located in Latin America, is a republic which has been governed by the communist regime since 1959, which is noted for its success in education. In Cuba, the duration of compulsory education is 9 years, primary education lasts 6 years and the first stage of the secondary education lasts 3 years. Students who successfully graduate from the second stage of the secondary education which lasts 3 years can attend to higher education institutions on the condition of having a ‘bachillerato’ diploma. Pre-school, primary and secondary teacher education programs last 5 years and utilize integrated teacher education model. In teacher education programs, which is comprised of Marxist philosophy, field knowledge, teaching knowledge and teaching practicum, practicum part is given a special importance. In Cuba, where teacher trainers have to have a 6 or 7 years of prior teaching experience in a non-tertiary institution, each teacher is also a researcher. Teachers who carry out an action research in every two years contribute to their professional development by presenting their research to their colleagues in an international congress.